2009
DOI: 10.1016/j.vetmic.2009.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated parapoxvirus ovis activates canine blood phagocytes and T lymphocytes

Abstract: Please cite this article as: Schütze, N., Raue, R., Büttner, M., Alber, G., Inactivated parapoxvirus ovis activates canine blood phagocytes and T lymphocytes, Veterinary Microbiology (2008Microbiology ( ), doi:10.1016Microbiology ( /j.vetmic.2009 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
4
13
0
6
Order By: Relevance
“…These results are consistent with the results of Schutze et al (2009), who investigated the immunostimulatory capacity of iPPVO on the innate immune system in vitro by evaluating the induction of the oxidative burst and the modulation of phagocytosis by canine blood leukocytes (PMNLs and monocytes) in dogs. After stimulation with iPPVO, the phagocytosis of fluorescein-isothiocyanate-labeled Listeria monocytogenes increased in canine blood, demonstrating that iPPVO stimulates PMNL functions in canine blood leukocytes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with the results of Schutze et al (2009), who investigated the immunostimulatory capacity of iPPVO on the innate immune system in vitro by evaluating the induction of the oxidative burst and the modulation of phagocytosis by canine blood leukocytes (PMNLs and monocytes) in dogs. After stimulation with iPPVO, the phagocytosis of fluorescein-isothiocyanate-labeled Listeria monocytogenes increased in canine blood, demonstrating that iPPVO stimulates PMNL functions in canine blood leukocytes.…”
Section: Discussionsupporting
confidence: 91%
“…However, in vitro experiments have shown that iPPVO stimulates both phagocytic and T-cell-dependent immune mechanisms directed against bacteria in canine blood leukocytes (Schutze et al 2009). In one study of horses, two commercial immunostimulants, iPPVO and inactivated Propionibacterium acnes, significantly enhanced the functions of phagocytic cells after ex vivo exposure to virulent Rhodococcus equi (Ryan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, stimulation with PMA did not show any differences between sera from distinct time points. Interestingly, in the presence of immune serum not only monocytes but also PMN 295 responded to iPPVO stimulation with oxidative burst, whereas samples supplemented with serum before treatment showed iPPVO-induced burst activity exclusively in monocytes as recently described (Schütze et al, 2009). Consistent with the time course of the antibody levels (see Fig.…”
Section: Detection and Characterization Of Ippvo-specific Antibodies supporting
confidence: 68%
“…Moreover, it is of interest to explore if iPPVO-specific antibodies are able to 80 contribute to the known immunostimulatory properties of iPPVO. We have recently shown in vitro stimulation of canine phagocytes by iPPVO (Schütze et al, 2009). Inactivated PPVO potently enhanced phagocytosis of Listeria by monocytes and PMN.…”
Section: Introductionmentioning
confidence: 99%